Diversity and biogeography of dinoflagellates in the Kuroshio region revealed by 18S rRNA metabarcoding - Wu, Yubei; Hirai, Junya; Zhou, Fanyu; Iwataki, Mitsunori; Jiang, Siyu; Ogawa, Hiroshi; Inoue, Jun; Hyodo, Susumu; Saito, Hiroaki (Frontiers in Marine Science, 2024)
Dinoflagellate is one of the most diverse and pervasive protists and a fundamental player in the marine food web dynamics and biogeochemical cycles. While possessing different nutritional strategies from purely autotrophy or heterotrophy to mixotrophy, some of them are also known as toxic harmful algal bloom (HAB) formers over the world. Despite their ordinariness, their diversity and biogeography are understudied in the open ocean compared with coastal region. As the first metabarcoding survey covering the Kuroshio current region from the offshore of Okinawa to the south of Honshu, we investigated the distribution of free-living dinoflagellates using the hypervariable V4 and V9 regions on 18S rRNA and their relation to ambient environments influenced by this oligotrophic but highly productive current in the northwest Pacific Ocean. We observed community structures differentiated by depth and nutrient concentrations. Most species annotated are autotrophic or mixotrophic and had a distribution correlated to warmer surface water, whereas heterotrophic species correlated to high nutrient levels or deeper layer. Our results also confirmed the overall high genetic diversity of dinoflagellates that decreased with depth and onshore. Most species present at stations offshore, and the relative abundance of HAB assemblages was lower at nutrient-rich stations on the continental shelf than stations influenced by the Kuroshio current, exhibiting the role of the Kuroshio transporting dinoflagellates including HAB species. To fully understand the dynamics of dinoflagellate communities in marine ecosystems, further seasonal monitoring is foremost for correlating dinoflagellates and environmental factors while completing the reference genomic database.